On the use of criminal law notions in determining state responsibility for genocide - Cassese, Antonio (Journal of international criminal justice, 2014)
On the face of it the 1948 Convention on Genocide appears to be a treaty that on the one hand obliges contracting states to criminalize and punish genocide in their domestic legal systems and, on the other, arranges for interstate judicial cooperation for the repression of genocide. The International Court of Justice (ICJ), in the Bosnia v. Serbia judgment, has instead held that the Convention, in addition to providing for the criminal liability of individuals, also imposes on contracting states as international subjects a set of obligations (to refrain from engaging in genocide, to prevent and punish the crime, and also to refrain for all those categories of conduct enumerated in Article III: conspiracy, incitement, attempt, complicity). This approach raises two questions: (i) is it warranted so to broaden states' responsibility? (ii) when applying such Article III categories to state responsibility, should an international court such as the ICJ that pronounces on interstate disputes rely upon criminal law categories to establish whether a state incurs responsibility for conspiracy, complicity, and so on? Or should it instead forge autonomous legal categories better suited to state responsibility? The author sets forth doubts about whether it is appropriate to transpose criminal law categories to the corpus of international law of state responsibility. In particular, his misgivings relate to the category of state complicity in genocide as set out by the Court: once the Court decided to transplant this criminal law category to state responsibility, arguably it should have relied upon the rigorous concept of complicity, as derived by international criminal courts from case law and the relevant practice of states, rather than apply a notion that finds no basis in international criminal law, in comparative criminal law or in state practice